Sheepstor. (1st January 2013) - Shutt, Nick; Bayly, Richard; Tingle, Liz
Abstract: This paper charts the development of one small rural parish's engagement in mission to visitors, from the inception of the original idea, its development, execution, and evaluation. It is a narrative with a beginning (a context), a middle (a collaboration) an end (a celebration) and a new beginning (which is ongoing). It is a reflection on mission in post-modern rural Britain; it is a little story which tells the big story.